IPv6 performance analysis on FreeBSD workstation using simple applications - Ettikan, K.; Ganapathy, V. (Springer Berlin Heidelberg, 2000)
The twenty five year- old Internet Protocol (IP) or known as IPv4, has its own history in connecting the world for information exchange. Its' new successor, IPv6 with promising functionality and capability is being designed to replace the predecessor. This paper analyses the performance of the new IP compared to old IP on dual stack implementation of KAME [7] FreeBSD [9] using ping and FTP application. Packet transmission time as been taken as the measurement metric. Test results of experiment shows that IPv6 performance is inferior to IPv4 and does not conform with the theoretical results.